2020
DOI: 10.47760/ijcsmc.2020.v09i10.012
|View full text |Cite
|
Sign up to set email alerts
|

Attack and Anomaly Detection in IoT Networks using Machine Learning

Abstract: For quite a few years now the name Internet of Things (IoT) has been around. IoT is a technology capable of revolutionizing our way of life, in sectors ranging from transportation to health, from entertainment to our interactions with government. Even this great opportunity presents a number of critical obstacles. As we strive to develop policies, regulations, and governance that form this development without stifling creativity, the increase in the number of devices and the frequency of that increase presents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…The random forest algorithm achieved the best accuracy of 99.5% among the others. While the methodology and the data samples were different from our study, as we used highly randomized data, the results for the above study, along with the other study of Thamataiselvi et al [15], was in line with our results too.…”
Section: Related Worksupporting
confidence: 90%
“…The random forest algorithm achieved the best accuracy of 99.5% among the others. While the methodology and the data samples were different from our study, as we used highly randomized data, the results for the above study, along with the other study of Thamataiselvi et al [15], was in line with our results too.…”
Section: Related Worksupporting
confidence: 90%
“…IoT-NID [25] Smart home, laptops, and smartphones Mirai, MITM, DoS, scanning, etc Autoencoder [28] IoT-23 [26] Smart home (real IoT devices) Mirai, Torii, and Gafgyt RF, NB, SVM, DT [27], autoencoder [28] ToN-IoT [30] Weather and industrial control sensors (MQTT)…”
Section: Doshi Et Al [14]mentioning
confidence: 99%
“…They have achieved up to 99% accuracy by applying the random forest (RF) classifier; however, the dataset used in this research was small (357,952 records) compared to other practical datasets. RF has also been claimed, in [22], as the best algorithm for detecting anomalies. Meanwhile, DL has shown better performance when dealing with large datasets.…”
Section: Related Workmentioning
confidence: 99%
“…They have improved this result to 99.99% by applying LSTM in [49]; however, F1-score is not mentioned in this research. Authors in [22,34] have reported RF as the best algorithm for detecting attacks with 100% and 99.50% accuracy, respectively. Authors in [37] have achieved accuracy with only 0.14% greater than our NN model.…”
Section: Accuracymentioning
confidence: 99%